Changes in lipid profiles induced by bisphenol A (BPA) in zebrafish eleutheroembryos during the yolk sac absorption stage. (May 2020) - Martínez, Rubén; Navarro-Martín, Laia; van Antro, Morgane; Fuertes, Inmaculada; Casado, Marta; Barata, Carlos; Piña, Benjamin
Abstract: Bisphenol A (BPA; 4, 4'-(propane-2, 2-diyl)diphenol) has been shown to act as an obesogen and to disrupt lipid metabolism in zebrafish eleutheroembryos (ZE). To characterize the consequences of this disruption, we performed a detailed lipidomic study using ZE exposed to different BPA concentrations (0, 4, 6 and 8 mg/L of BPA) from day 2 to up to day 6 post fertilization (dpf). Total lipids at 4, 5 and 6 dpf were extracted by Folch method and analyzed by high-performance thin layer chromatography (HPTLC) as wide-range preliminary screening. Selected conditions (0 and 6 mg/L of BPA) were used to obtain a high-quality lipid profile using ultra high-performance liquid chromatography/time-of-flight mass spectrometry (UHPLC-TOFMS). BPA exposed ZE exhibited increased amounts of triglycerides (TG), diglycerides (DG), phosphatidylcholines (PC) and phosphatidylinositols (PI), regarding the control group. Analysis of time- and BPA exposure-related patterns of specific lipid species showed a clear influence of unsaturation degree (mostly in DG and PC) and/or fatty acid chain length (mostly in TG and PC derivatives) on their response to the presence of BPA. A decreased yolk-sac and energy consumption in exposed individuals appeared as the main reason for the observed BPA-driven effects. Integration of these results with previous morphological, biochemical, transcriptomic, metabolomic and behavioral data suggests a disruption of different signalling pathways by BPA that starts at very low BPA concentrations, whose effects propagate across different organization levels, and that cannot be only explained by the relatively weak estrogenic effect of BPA. Graphical abstract: Image 1 Highlights: BPA induces yolk-sac and lipid retention in late zebrafish eleutheroembryos. Most retained lipids were related to energy metabolism. Fate of individual lipids was determined by their physicochemical characteristics. Lipidomic changes were linked to most BPA adverse effects on fish eleutheroembryos.